2018
DOI: 10.1182/bloodadvances.2018019117
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of cardiovascular disease among hematopoietic cell transplantation survivors

Abstract: • We identified distinct groups of HCT survivors at low, intermediate, and high risk of developing late-occurring CVD.• The prediction model had good discrimination across outcomes and was validated in an external cohort of HCT survivors. 2) and 2.9-fold (95% confidence interval, 1.9-4.6) risk of developing CVD (referent group: low risk). These validated models provide a framework on which to modify current screening recommendations and for the development of targeted interventions to reduce the risk of CVD af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 57 publications
0
58
1
2
Order By: Relevance
“…There are many studies that have shown a higher prevalence of coronary artery disease and congestive heart failure in the cancer survivors [ 37 - 45 ]. The increased cardiovascular risk in the cancer survivors have been attributed secondary to a specific treatment for their cancers, such as hematopoietic stem cell transplantation [ 37 ], radiation or anthracycline therapy [ 38 - 41 ], use of trastuzumab, sorafenib and sunitinib, bevacizumab and other agents [ 42 - 44 ], and other cardiotoxicities [ 45 ]. Additionally, suboptimal control of multiple cardiovascular risk factors, such as hypertension, diabetes and hyperlipidemia, was also observed in the cancer survivors [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies that have shown a higher prevalence of coronary artery disease and congestive heart failure in the cancer survivors [ 37 - 45 ]. The increased cardiovascular risk in the cancer survivors have been attributed secondary to a specific treatment for their cancers, such as hematopoietic stem cell transplantation [ 37 ], radiation or anthracycline therapy [ 38 - 41 ], use of trastuzumab, sorafenib and sunitinib, bevacizumab and other agents [ 42 - 44 ], and other cardiotoxicities [ 45 ]. Additionally, suboptimal control of multiple cardiovascular risk factors, such as hypertension, diabetes and hyperlipidemia, was also observed in the cancer survivors [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been several attempts at developing risk prediction models for identifying patients at highest risk for anthracycline-related cardiomyopathy. Clinical risk prediction models have yielded modest predictive power for identifying patients at risk for anthracycline-related cardiomyopathy ( 31 , 78 ), resulting in studies that combined genetic variants with clinical and demographic variables to improve the ability to disriminate anthracycline-exposed survivors by their risk of developing cardiomyopathy. Visscher et al ( 25 ) combined multiple variants from drug biotransformation genes together with clinical risk factors into a prediction model and classified patients into 3 risk groups.…”
Section: Prediction Of Anthracycline-related Cardiomyopathymentioning
confidence: 99%
“…Notably, CVD is also a significant morbidity in HSCT patients ( Armenian et al., 2017 ). As in CHIP, HSCT patients exhibit heart failure and coronary artery disease; however, the mechanisms underlying this presentation are not known ( Armenian et al., 2018 ). In a model of Tet2 deficiency in atherosclerosis-prone low-density lipoprotein receptor -deficient mice, macrophages secreting IL-1β exacerbate atherosclerosis ( Fuster et al., 2017 ).…”
Section: Main Textmentioning
confidence: 99%